INTERACTION OF POLY(I) WITH ETHIDIUM BROMIDE (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
The interaction of ethidium bromide (EtBr) with polyinosine (poly(I)) has been studied by absorption and fluorescence spectroscopy methods. Our investigations have shown that titration experiments within raising of poly(I) concentration the maximum of absorption in visible region decreases and is shifted toward longer wavelength region. According to the obtained results it is assumed that poly(I) in physiological conditions exists both in single- and double-stranded helices formed contemporaneously. The studies are relevant to understand the polyinosine structure in aqueous-salt solution.
Keywords: poly(I), ethidium bromide, complex-formation, absorption and fluorescence spectra